A Tb2Fe3 Pyramid Single‐Molecule Magnet with Ferromagnetic Tb‐Fe Interaction. Issue 4 (6th March 2019) - Li, Han; Meng, Xixi; Wang, Mengmeng; Wang, Yu‐Xia; Shi, Wei; Cheng, Peng
Summary of main observation and conclusion: The influence of magnetic interactions to the magnetization dynamics was well experimentally studied in a 3d‐4f single‐molecule magnet (SMM) [Tb III 2 Fe III 3 ( μ 5 ‐O)L2 (NO3 )4 Cl] (1, H4 L = N, N, N ', N '‐tetrakis(2‐hydroxyethyl)ethylene diamine) and its diamagnetic‐ ion‐diluted samples. Significant ferromagnetic coupling between Tb III and Fe III ions and SMM behavior of 1 were observable, which proved clearly that the magnetic interaction between 3d‐4f spin carriers has also an excessive impact on fine‐tuning the magnetization dynamic behaviors of 3d‐4f complexes. Abstract : The influence of ferromagnetic Tb‐Fe interaction to the single‐molecule magnet behavior in a Tb2 Fe3 Pyramid was studied.